The SPACE of Developer Productivity: There's more to it than you think - Forsgren, Nicole; Storey, Margaret-Anne; Maddila, Chandra; Zimmermann, Tom; Houck, Brian; Butler, Jenna (ACM Queue, 2021)
Developer productivity is about more than an individual's activity levels or the efficiency of the engineering systems relied on to ship software, and it cannot be measured by a single metric or dimension. The SPACE framework captures different dimensions of productivity, and here we demonstrate how this framework can be used to understand productivity in practice and why using it will help teams better understand developer productivity and create better measures to inform their work and teams.